Pharmacokinetics of acyclovir suspension in infants and children. - Sullender, W M (1987)
Eighteen children from 3 weeks to 6.9 years of age were given an oral acyclovir suspension for herpes simplex or varicella-zoster virus infections. Thirteen patients who were 6 months to 6.9 years old received 600 mg/m2 per dose, and three infants and two children less than 2 years old were given 300 mg/m2 per dose. The drug was given four times a day, except to one infant who was treated with three doses a day. Among the 13 children who received the 600-mg/m2 dose, the maximum concentration in plasma (Cmax) was 0.99 +/- 0.38 microgram/ml (mean +/- standard deviation), the time to maximum concentration (Tmax) was 3.0 +/- 0.86 h, the area under the curve (AUC) was 5.56 +/- 2.17 micrograms.h/ml, and the elimination half-life (t1/2) was 2.59 +/- 0.78 h. The three infants less than 2 months of age who received the 300-mg/m2 dose had a Cmax of 1.88 +/- 1.11 micrograms/ml, a Tmax of 4.10 +/- 0.48 h, an AUC of 6.54 +/- 4.32 micrograms.h/ml, and a t1/2 of 3.26 +/- 0.33 h. The acyclovir suspension was well tolerated by young children. No adverse effects requiring discontinuation of the drug occurred.